DOPANT AND MAGNETIC FIELD EFFECTS ON HEAT TRANSFER OF PHASE CHANGE MATERIAL (PCM) BASED LAURIC ACID - Anggraini, Yunita
To meet the challenge of the energy crisis, efficient thermal energy storage must be adopted. According to several reference studies, adding magnetic and nonmagnetic dopants to phase change materials (PCM) can enhance the rate of heat transfer and thereby decrease the phase transition time in latent energy storage. The use of magnetic dopants and magnetic fields to influence the PCM phase transition process is a key component in optimizing the performance of materials as latent heat energy storage, although no reference studies have been published thus far. In the experimental study, we investigated the influence of magnetic dopants on the heat discharge of the phase change material (PCM) based on lauric acid (LA), known as magnetic-composite LA, as well as the use of an external magnetic field provided by the permanent magnet. Along with this, thermal conductivity and viscosity measurements were also performed in relation to the heat discharge. The two dopants employed are Fe3O4 and CoFe2O4, each with three concentration values (2 wt.%, 5 wt.%, and 10 wt.%), while the variation in magnetic field values is generated by arranging permanent magnets. In the solidification study, the magnetic fields (H) were 67-74 mT (H1), 117-142 mT (H2), and 175-215 mT (H3). Magnetic field variations employed in thermal conductivity/viscosity studies were 54-71 mT (H1) and 90-118 mT (H2). The determined solidification time parameters include solidification time (tf) which indicates the start time of the heat release process by the growth of crystal nuclei, inflection time (ti) which indicates the end time of the heat release process or liquid to solid phase transition, and total crystallisation time (tc) which is calculated as the difference between ti and tf. Compared with pure LA, the addition of dopants as well as the application of a magnetic field generally results in a decrease in tf, ti, and tc. The maximum time saving of tc is 42% and 33% for Fe3O4-composite LA and CoFe2O4-composite LA, respectively, and these values are obtained at dopant concentrations 5 wt.% for Fe3O4-composite LA and 10 wt.% for CoFe2O4- composite LA, and both are obtained in the highest magnetic field intensity. The solidification parameters are then correlated with liquid thermal conductivity data. High thermal conductivity can reduce the time lag between the sample and its surroundings, resulting in a faster phase transition rate. The liquid thermal conductivity was measured at an average temperature of 55 °C above the melting point of LA, while the solid thermal conductivity was measured at room temperature at 25 °C. In the absence of a magnetic field, the addition of dopants results in liquid or solid phase thermal conductivity of magnetic-composite LA values larger than LA. The thermal conductivity of the magnetic-composite LA in both phases increases with dopant concentration. In this case, the liquid-phase thermal conductivity of the CoFe2O4-composite LA is greater than that of the Fe3O4-composite LA. The application of a magnetic field produces nonmonotonous increases in thermal conductivity with the increasing magnetic field up to a critical magnetic field (CMF), and the value will decrease in fields above CMF. The CMF value depends on the concentration and type of dopant. For dopant concentrations of 2 and 5 wt%, CMF for Fe3O4-composite LA occurs in H1 and less than H1 for CoFe2O4-composite LA. At a maximum dopant concentration of 10 wt%, CMF occurs in a magnetic field over H2. In this study, the highest thermal conductivity ratio to LA was 122% and 120% for Fe3O4-composite LA and CoFe2O4-composite LA, respectively, which were obtained at the maximum dopant concentrasion and magnetic field. Viscosity is a parameter that indirectly influences the thermal conductivity value. At zero magnetic field, the addition of dopant to LA results in an increase in viscosity, and its value increases with increasing dopant concentration. In addition, the effect of temperature on the viscosity of the LA magnetic composite was also evaluated, and the results revealed that the viscosity value dropped as temperature increased. At all concentration and temperature values, the viscosity of the CoFe2O4-composite LA composite is greater than that of the Fe3O4-composite LA. The influence of the magnetic field on the viscosity of magnetic-composite LA is non-monotonic, similar to thermal conductivity. The viscosity value increases to the optimum field, and the value depends on the concentration and type of dopant. For the Fe3O4-composite LA, the viscosity values for all dopant concentrations decrease with the magnetic field and are smaller than LA. For the CoFe2O4- composite LA at concentrations of 2 and 5 wt.%, the viscosity value decreases with increasing magnetic field, whereas at a concentration of 10 wt.%, the viscosity increases in the H1 field and then decreases in the H2 field. The effectiveness of magnetic nanoparticle dopants and magnetic fields in the heat release process of magnetic-composites LA is strongly related to thermal conductivity and viscosity, and it is affected by dopant concentration and type. In the absence of magnetic field, the bigger particle size of CoFe2O4 relative to Fe3O4 is responsible for the higher viscosity of CoFe2O4-composite LA and causes its thermal conductivity to be greater than that of Fe3O4-composite LA. When the magnetic field is applied to a sample, the magnetised particles can form chain-like structures due to strong dipolar interactions. The chain-like structure aligned along the direction of the magnetic field provides favourable conditions for heat transfer, which is responsible for the increase in thermal conductivity and viscosity. The number and density of chain structures increase as the dopant concentration increases. The chain strength is determined by the saturation magnetization of the dopant and the magnetic field, where the higher the saturation magnetization of the dopant, the higher the chain strength. The magnetic field to reach this saturation state may be a barrier to chain formation, and this is closely related to the viscosity of the suspension because higher viscosity inhibits chain formation. At high magnetic fields, the chains are closer together and thicker at the center of the field which will produce a zippering condition before the anisotropic structure. This condition will reduce the heat transfer rate of magnetic-composite LA as indicated by a decrease in thermal conductivity and viscosity.